Scaffolds de óxido de titânio e biosilicato para aplicações médicas e odontológicas obtidos com o uso de partículas orgânicas - Fernandes, Mérilin Cristina dos Santos (Universidade Federal de São Carlos, 2015)
Scaffolds are an alternative to natural grafts to help bone regeneration in large bone defects. Regardless of the material chosen for its manufacture, scaffold should have a suitable dimensional microenvironment to promote osteogenesis and an appropriate mechanical stability for the defect site. Titanium dioxide (TiO2) is a highly biocompatible ceramic with good osteoconductive properties and high reliability mechanical; biosilicate has excellent bioactivity level. Thus, in order to fabricate scaffolds allying positive mechanical strength and bioactivity characteristics necessary to a good product, biosilicate was pioneered combined with TiO2. Among the techniques available for scaffolds production, the sacrificial template method, in which porosity is generated by thermal elimination of organic materials added to the ceramic matrix, has a low cost, simplicity and versatility. Different sacrificial agents were tested and the presentation of sawdust as a promising material in scaffolds manufacture proved to be innovative and satisfactory. Microstructural analyzes showed that controlled addition of wood sawdust amounts generated a homogeneous and highly interconnected pore structure with 63% apparent porosity and an average pore size higher than 200 μm. Bioactivity tests in SBF showed that after 4 days of immersion has already observed starting precipitation of hydroxycarbonate apatite in products with biosilicate, and after 12 days of immersion the scaffold was fully covered by this mineral. Mechanical tests allowed evaluating the scaffolds behavior when they are requested by tensile efforts, and revealed for samples with maximum porosity obtained, higher values of strength for samples containing biosilicate. The produced scaffolds had success in the pore structure obtained by sacrificial template method being biosilicato addition guaranteed improvements in bioactivity and mechanical strength.
Titanium dioxide and biosilicate scaffolds prepared with organic particles for medical and dental applications
Keywords: TiO2; Porosidade; Biomaterial; Bioatividade; Regeneração óssea; ENGENHARIAS::ENGENHARIA BIOMEDICA::ENGENHARIA MEDICA